Access to finance employment growth and firm performance of South Asia firms - Anh Tuan Bui; Linh Chi Pham; Thi Khanh Van Ta (Global Labor Organization (GLO), 2021)
Using firm-level data on 11,000 companies across seven countries in South Asia, this paper explores the effects of access to finance on employment growth and performance at the firm level. The paper focuses on how the impact of financing obstacles varies across firm sizes. The results show that higher obstacles in access to finance reduces employment growth and performance for firms of all sizes, especially micro and small firms. We find significant differences between firms with less than 10 employees and small firm, which suggests that significant reforms are needed to drive micro firm growth to small and medium enterprises.
Keywords: J21; J41; M51; 330; Access to finance obstacles; employment growth; Total factor of productivity